Concentration dependent effects of hydrogen peroxide on lens epithelial cells. Issue 9 (1st September 1999) - Ohguro, Nobuyuki; Fukuda, Masakatsu; Sasabe, Tetsuo; Tano, Yasuo
Abstract : AIMS: To evaluate the effects of hydrogen peroxide exposure on the survival and proliferation of cultured lens epithelial cells. METHODS: TOTL-86 cells, a line of rabbit lens epithelial cells, were used. The survival and proliferation of TOTL-86 cells were quantified by a rapid colorimetric assay (MTT assay). To determine the effects of hydrogen peroxide, TOTL-86 cells were exposed to different concentrations of hydrogen peroxide. To determine the effect of cell numbers on the survival and proliferation of TOTL-86 cells at a fixed concentration of hydrogen peroxide, different numbers of cells were plated and exposed to hydrogen peroxide. To determine whether there is a synergistic effect between hydrogen peroxide and EGF, bFGF, PDGF-AA, and insulin, TOTL-86 cells were exposed to hydrogen peroxide combined with one of these growth factors. RESULTS: High levels (1 mM) of hydrogen peroxide killed TOTL-86 cells and sublethal levels (100 μM) suppressed their proliferation. From 1 nM to 1 μM of hydrogen peroxide, there was a dose dependent increase in the cell numbers. The initial seeded cell number dramatically affected the response to hydrogen peroxide. Although growth factors showed no synergistic effects with hydrogen peroxide on proliferation, both EGF and insulin, but not bFGF or PDGF, rescued TOTL-86 cells from the sublethal effect. CONCLUSION: Hydrogen peroxide in cooperation with some growth factors plays an important role in the proliferation of lens epithelial cell.